Predicting potential habitat distribution of the invasive chromolaena odorota L. (Siam weed) in the Philippines using Maximum Entropy Model - Gatchalian, Regina Victoria H. (Department of Biology and Environmental Science, College of Science, University of the Philippines Cebu, 2021)
Invasive alien species are considered as a major threat to ecosystem functions and local diversity. It will continue to do so as transmission of biological invasions are perpetuated by the rapid increase in global trade, travel, and tourism. The study used MaxEnt modeling to predict habitats suitable for Chromolaena odorata (Siam weed), one of the seven worst invasive plant species in the Philippines. The modeling procedure used 118 occurrence records of C. odorata in the Philippines and ten Worldclim bioclimatic variables. This study provides a reference and a starting point for forecasting, monitoring, or controlling C. odorata from spreading and having a negative impact on biodiversity. The MaxEnt model proved to be reliable (Area under the Receiver Operating Curve=0.913). Of the ten bioclimatic variables tested, Jackknife test revealed that the four variables, namely; mean diurnal range, temperature annual range, temperature seasonality, and precipitation of the coldest quarter had the most contribution to model that predicted the potential distribution of C. odorata. Moreover, the MaxEnt model revealed that the potential suitable habitat area of C. odorata under current climate conditions has limited potential distribution, occurring mainly in the Zamboanga Peninsula and the provinces of Lanao del Norte and Misamis Oriental of Northern Mindanao. Therefore, current management of the species should be prioritized in these areas. Other factors such as soil, topography, dispersal mechanism and agent, anthropogenic disturbance must be considered in future studies to improve model performance.